Back Cover: Solar RRL 2∕2017. Issue 2 (February 2017) - Yu, LePing; Grace, Tom; Jazi, Mahnaz Dadkhah; Shearer, Cameron; Shapter, Joseph
Abstract : Heterojunction solar cells based on silicon and single walled carbon nanotube (CNT) transparent conducting films are a typical example of new generation solar cells. Until now, these solar cells have been prepared with very small areas that can capture the sunlight. Simply increasing the working area of the device leads to a significant efficiency loss, due to an inherent limitation of the conductivity of the top, transparent CNT electrode. As with current commercial cells, additional conductive metal grids strategically placed on the surface can act as current collecting front contacts, which overcome this efficiency loss issue. Here, Shapter et al. (article No.1600026 ) demonstrate the grid design of the metal front contact, which has been optimized and as a result, the solar cell performance more than doubled. These results suggest that employing a patterned metal front contact is a scalable method to achieve new solar cells with efficiencies above 10 %. This approach has the potential to be applied in any other solar cells, to overcome efficiency loss with increasing surface area.